Type 2 diabetes as a factor influencing the professional activity of patients after acute coronary syndrome - Niedziałek, Jarosław; Mizerski, Grzegorz; Gorczyca, Rafał; Jaroszyński, Andrzej; Zagórski, Jerzy (Polish Journal of Public Health, 2012)
Introduction. Type 2 diabetes (Diabetes mellitus typus 2 – DM t.2) is a civilization disease of a social character exerting health and socio-economic effects difficult to overestimate. Diabetes deteriorates the course of many diseases, especially those of a cardiovascular nature.Aim. The objective of the presented study was determination of the effect of type 2 diabetes on the occupational activity of patients who had undergone an Acute Coronary Syndrome (ACS).Material and methods. The study covered 8,640 patients who had undergone an ACS (5,642 males and 2,998 females) treated at the Spa Sanatorium for Farmers in Nałęczów during the period 2005-2009.Results. Among those who had undergone an ACS and had been occupationally active before the event, there were 50.4% of patients with diabetes and 56.7% without diabetes (p